Social Change and the Role of Sufi Orders in Indonesia: A Systematic Literature Review - Hanung Sito Rohmawati; Zulkifli Zulkifli (Teosofia: Indonesian Journal of Islamic Mysticism, 2024)
Sufi orders have made a significant contribution to Indonesian society; however, systematic literature reviews on this topic remain limited. This article aims to examine the role of Sufi orders in supporting social change in Indonesia. Using the SLR and PRISMA guidelines, this study reviews journal articles from Google Scholar published between 2015 and 2024. The analysis of 14 articles indicates that Sufi orders in Indonesia play a significant role in socio-political, educational, philanthropic, economic, personal, and spiritual transformation. The reviewed articles demonstrate that Sufi orders serve as effective agents of social change, employing adaptive, evolutionary, and contextually relevant approaches to address societal needs. This research provides a comprehensive perspective on Sufi orders’ contribution to social change, offering practical methods to support sustainable social transformation in Indonesia. Further studies can conduct more comprehensive SLRs with broader scopes, including more varied databases. Contribution: This paper contributes to understanding the positive contributions made by Sufi orders to Indonesian society in terms of socio-political, educational, philanthropic, economic, personal, and spiritual transformation. It also provides a basis for further study to review the role of Sufi orders from different perspectives.